Das Forschungsprojekt „PoWi-Kids – Politisches Wissen von Kindern“ im Kontext politikdidaktischer Forschungslinien - Becher, Andrea; Gläser, Eva (Politische Bildung im Sachunterricht Potenziale – Positionen – Perspektiven)

Zukunftspop - Popzukunft. Kurze Anmerkungen zu Konstanten der Popmusikkulturen. - Jacke, Christoph (Hits & Storys. 20 Jahre rock'n'popmuseum.)
Keywords: Zukunft; Popmusik; Medien; Technik; Genre; Wandel; Kulturen; Museum; Geschichte; Popular Music Studies

Theorien des digitalen Kapitalismus. Arbeit, Ökonomie, Politik und Subjekt - Quast, Julia (Zeitschrift für Genozidforschung)

Music and Narrative in Art Exhibition Audio Guides: "Beckmann & Amerika" - Mildorf, Jarmila (Music and its Narrative Potential)

Stabilisierung von O2-sensitiven Photolumineszenzsignalen durch Temperaturvariation - Kothe, Linda; Ester, Stephan; Poeplau, Michael; Wengenroth, Marc; Tiemann, Michael (Proceedings 22. GMA/ITG-Fachtagung Sensoren und Messsysteme 2024)
In dieser Arbeit werden Untersuchungen zur sauerstoffabhängigen Photolumineszenz von Zink-Zinn-Oxid-Partikeln präsentiert, welche perspektivisch für die optische Sauerstoffdetektion eingesetzt werden sollen. Zink-Zinn-Oxid zeigt eine sauerstoffabhängige Photolumineszenz im sichtbaren Spektralbereich und wird hier als eine photostabile Alternative zu den kommerziell verfügbaren metallorganischen Verbindungen vorgestellt. Der Fokus liegt dabei auf dem Einfluss der Temperatur auf die Sauerstoffsensitivität der Photolumineszenz. Wir zeigen, dass bereits leichte Temperaturerhöhungen zu einer signifikanten Verbesserung der Sauerstoffsensitivität der Photolumineszenz führen und gleichzeitig die Signalqualität erhöhen.

Non-symmetric GHZ states; weighted hypergraph and controlled-unitary graph representations - Zakaryan, Hrachya; Revis, Konstantinos-Rafail; Raissi, Zahra (arXiv:2408.02740)
Non-symmetric GHZ states ($n$-GHZ$_α$), characterized by unequal superpositions of $|00...0>$ and $|11...1>$, represent a significant yet underexplored class of multipartite entangled states with potential applications in quantum information. Despite their importance, the lack of a well-defined stabilizer formalism and corresponding graph representation has hindered their comprehensive study. In this paper, we address this gap by introducing two novel graph formalisms and stabilizers for non-symmetric GHZ states. First, we provide a weighted hypergraph representation and demonstrate that non-symmetric GHZ states are local unitary (LU) equivalent to fully connected weighted hypergraphs. Although these weighted hypergraphs are not stabilizer states, we show that they can be stabilized using local operations, and an ancilla. We further extend this framework to qudits, offering a specific form for non-symmetric qudit GHZ states and their LU equivalent weighted qudit hypergraphs. Second, we propose a graph formalism using controlled-unitary (CU) operations, showing that non-symmetric qudit GHZ states can be described using star-shaped CU graphs. Our findings enhance the understanding of non-symmetric GHZ states and their potential applications in quantum information science.

Drivers of Digital Realities for Ongoing Teacher Professional Learning - Trevisan, O.; Christensen, R.; Drossel, Kerstin; Friesen, S.; Forkosh-Baruch, A.; Phillips, M. (Technology, Knowledge and Learning)
Abstract In an era marked by the widespread use of digital technology, educators face the need to constantly learn and develop their own new literacies for the information era, as well as their competencies to teach and apply best practices using technologies. This paper underscores the vital role of ongoing teacher professional learning (OTPL) with a focus on reflective practices and pedagogical reasoning and action (PR&A) in shaping education quality and equity. Examining three key drivers of educational transformation—big data and learning analytics, Artificial Intelligence (AI), and shifting teacher identities—the paper explores their overall impact on teacher practices. This paper emphasizes technology as a crucial boundary object, a catalyst of educational transformation, when used to foster communication and professional growth. To this end, three boundary objects are identified, namely dashboards, AI-driven professional learning environments, and digital communities of practice. These tools illustrate technology’s capacity to mediate relationships between transformative educational drivers and teacher practices, offering a pathway to navigate shifting perspectives on OTPL. With a theoretical foundation in equitable education, the paper provides insights into the intricate relationship between boundary objects and evolving educational dynamics. It highlights technology's pivotal role in achieving both quality and equitable education in the contemporary educational landscape. It presents a nuanced understanding of how specific tools may contribute to effective OTPL amid rapid educational transformations.

Gas Sensing with Nanoporous In2O3 under Cyclic Optical Activation: Machine Learning-Aided Classification of H2 and H2O - Baier, Dominik; Krüger, Alexander; Wagner, Thorsten; Tiemann, Michael; Weinberger, Christian (Chemosensors)
Clean hydrogen is a key aspect of carbon neutrality, necessitating robust methods for monitoring hydrogen concentration in critical infrastructures like pipelines or power plants. While semiconducting metal oxides such as In2O3 can monitor gas concentrations down to the ppm range, they often exhibit cross-sensitivity to other gases like H2O. In this study, we investigated whether cyclic optical illumination of a gas-sensitive In2O3 layer creates identifiable changes in a gas sensor´s electronic resistance that can be linked to H2 and H2O concentrations via machine learning. We exposed nanostructured In2O3 with a large surface area of 95 m2 g-1 to H2 concentrations (0-800 ppm) and relative humidity (0-70%) under cyclic activation utilizing blue light. The sensors were tested for 20 classes of gas combinations. A support vector machine achieved classification rates up to 92.0%, with reliable reproducibility (88.2 ± 2.7%) across five individual sensors using 10-fold cross-validation. Our findings suggest that cyclic optical activation can be used as a tool to classify H2 and H2O concentrations.
Keywords: resistive gas sensor; chemiresistor; semiconductor; metal oxide; In2O3; mesoporous; hydrogen; humidtiy; machine learning

Isostructural Series of a Cyclometalated Iron Complex in Three Oxidation States - Steube, Jakob; Fritsch, Lorena; Kruse, Ayla; Bokareva, Olga S.; Demeshko, Serhiy; Elgabarty, Hossam; Schoch, Roland; Alaraby, Mohammad; Egold, Hans; Bracht, Bastian; Schmitz, Lennart; Hohloch, Stephan; et al. (Inorganic Chemistry)
An isostructural series of FeII, FeIII, and Fe(IV)complexes [Fe(ImP)2]0/+/2+ utilizing the ImP 1,1′-(1,3-phenylene)-bis(3-methyl-1-imidazol-2-ylidene) ligand, combining N-heterocy-clic carbenes and cyclometalating functions, is presented. The strong donor motif stabilizes the high-valent Fe(IV) oxidation state yet keeps the FeII oxidation state accessible from the parent Fe(III)compound. Chemical oxidation of [Fe(ImP)2]+ yields stable [FeIV(ImP)2]2+. In contrast, [FeII(ImP)2]0, obtained by reduction,is highly sensitive toward oxygen. Exhaustive ground state characterization by single-crystal X-ray diffraction, 1H NMR,Mössbauer spectroscopy, temperature-dependent magnetic measurements, a combination of X-ray absorption near edge structureand valence-to-core, as well as core-to-core X-ray emission spectroscopy, complemented by detailed density functional theory (DFT) analysis, reveals that the three complexes[Fe(ImP)2]0/+/2+ can be unequivocally attributed to low-spin d6, d5, and d4 complexes. The excited state landscape of the Fe(II) and Fe(IV) complexes is characterized by short-lived 3MLCT and 3LMCT states, with lifetimes of 5.1 and 1.4 ps, respectively. In the FeII-compound, an energetically low-lying MC state leads to fast deactivation of the MLCT state. The distorted square-pyramidal state, where one carbene is dissociated, can not only relax into the ground state, but also into a singlet dissociated state. Its formation was investigated with time-dependent optical spectroscopy, while insights into its structure were gained by NMR spectroscopy.

Schulisches Wohlbefinden von Schüler*innen der Sekundarstufe I in inklusiven Lerngruppen – Analysen zum Entwicklungsverlauf an der Laborschule Bielefeld - Marker, Rabea; Kullmann, Harry; Zentarra, Dominik; Geist, Sabine; Lütje-Klose, Birgit (Unterrichtswissenschaft)

Schulisches Wohlbefinden von Schüler*innen der Sekundarstufe I in inklusiven Lerngruppen – Analysen zum Entwicklungsverlauf an der Laborschule Bielefeld - Marker, Rabea; Kullmann, Harry; Zentarra, Dominik; Geist, Sabine; Lütje-Klose, Birgit (Unterrichtswissenschaft)

„halb und halb“ – Hybride Edition als Kompromiss? Eine Studie zu Methodik, Möglichkeiten und Grenzen in der hybriden Musikedition am Beispiel der Edition von Ludwig Baumanns „Kantate. Den Gefallenen zum Gedächtnis, den Trauernden zum Trost“ - Ried, Dennis
Vor etwa 20 Jahren haben hybride Editionen in der Musikwissenschaft Einzug gehalten. Es sind in erster Linie Langzeitprojekte mit Laufzeiten von über 15 Jahren (z. ,B. OPERA, RWA, EWK, BAZ-GA) die diese Form der Edition verwenden. Dennoch gibt es kaum Forschungsliteratur zu diesem Thema. Auch die immer wieder verwendete Forschungssoftware "Edirom" hat bislang weder eine ausreichende Dokumentation erfahren noch ist sie ausgiebig diskutiert worden. Zudem fehlt eine kritische Betrachtung des Phänomens Önline-Portal", welches gerade in der Musikphilologie immer häufiger in Erscheinung tritt. Von der Frage ausgehend, ob die hybride Edition ein Kompromiss aus traditioneller und digitaler Edition darstellt, unternimmt Dennis Ried erstmals den Versuch, den Status quo hybrider (Musik-)Editionen zu eruieren, zu dokumentieren und kritisch zu hinterfragen. "Hybrid" wird dabei stets als Zusammenspiel von Änalogem" und "Digitalem" betrachtet. Anders als traditionelle Dissertationsschriften ist diese Arbeit in zwei Teile gegliedert, wovon der erste aus einer exemplarisch angeführten und quasi eigenständigen wissenschaftlich-kritischen Edition besteht. Im zweiten Teil wird diese dann aktiv in die Theoriebildung eingebunden, um methodische Fragen gezielt erörtern zu können. Ergänzt wird die Dissertationsschrift durch eine auf Zenodo publizierte digitale Datensammlung.
Keywords: Musikwissenschaft; Digitale Edition; Musikphilologie

A large deformation gradient theory for glassy polymers by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Cold forming of polycarbonate films results in the formation of shear bands in the necking zone. The numerical results obtained from standard viscoplastic material models exhibit mesh size dependency, requiring mathematical regularization. For this purpose, we present in this work a large deformation gradient theory for a viscoplastic isotropic material model published before. We extend our model to a micromorphic model by introducing a new micromorphic variable as an additional degree of freedom along with its first gradient. This variable represents a microequivalent plastic strain. The relation between the macroequivalent plastic strain and the micromorphic variable is accomplished by a micromorphic coupling modulus. This coupling forces proximity between the macro- and microvariables, leading to the targeted regularization effect. The micromorphic model is implemented as a three-dimensional initial boundary value problem in an in-house finite element tool. The analysis is performed for both uniaxial and biaxial specimens. The provided numerical examples show the ability of our model to regularize shear bands within the specimens and address the issue of localization.

Facetten von ḏimma. Altbekanntes und Neues - Kokew, Stephan Matthias (Cibedo-Beiträge zum Gespräch zwischen Christen und Muslimen)

Cai, Hong (2022): Bedarfsanalysen für einen berufsbegleitenden Fremdsprachenunterricht am Beispiel von Deutsch als Fremdsprache. München: IUDICIUM Verlag. ISBN: 978-3-86205-625-5. 382 Seiten. 48,00 €. - Prikoszovits, Matthias (Zeitschrift für Interkulturellen Fremdsprachenunterricht (ZIF))

Aus Geschehen ein Ereignis formen: Auswählen, Werten, Sortieren in der Geschichtserzählung - Süßmann, Johannes (Ordnungssysteme. Auswählen, Werten, Sortieren in den Kulturwissenschaften)
Keywords: Geschichtstheorie; Ereignisbildung; Begriffsbildung; Erzählung; Narratologie

Lernprozessanregende Aufgaben in der Lehrkräftebildung: Förderung von Reflexions- und Medienkompetenz mit Fellinis „8 ½“ - Aßmann, Sandra; Wiethoff, Christoph (Medien – Bildung – Forschung. Integrative und interdisziplinäre Perspektiven)

Künstliche Intelligenz im (Fach-)Unterricht - Einsatz von ChatGPT bei der Fallarbeit im Pädagogikunterricht - Engemann, Mario (Medien - Bildung - Forschung. Integrative und interdisziplinäre Perspektiven)

Grundschulforschung meets Kindheitsforschung reloaded

Hardness of approximation for ground state problems - Gharibian, Sevag; Hecht, Carsten (arXiv:2411.04874)
After nearly two decades of research, the question of a quantum PCP theorem for quantum Constraint Satisfaction Problems (CSPs) remains wide open. As a result, proving QMA-hardness of approximation for ground state energy estimation has remained elusive. Recently, it was shown [Bittel, Gharibian, Kliesch, CCC 2023] that a natural problem involving variational quantum circuits is QCMA-hard to approximate within ratio N^(1-eps) for any eps > 0 and N the input size. Unfortunately, this problem was not related to quantum CSPs, leaving the question of hardness of approximation for quantum CSPs open. In this work, we show that if instead of focusing on ground state energies, one considers computing properties of the ground space, QCMA-hardness of computing ground space properties can be shown. In particular, we show that it is (1) QCMA-complete within ratio N^(1-eps) to approximate the Ground State Connectivity problem (GSCON), and (2) QCMA-hard within the same ratio to estimate the amount of entanglement of a local Hamiltonian's ground state, denoted Ground State Entanglement (GSE). As a bonus, a simplification of our construction yields NP-completeness of approximation for a natural k-SAT reconfiguration problem, to be contrasted with the recent PCP-based PSPACE hardness of approximation results for a different definition of k-SAT reconfiguration [Karthik C.S. and Manurangsi, 2023, and Hirahara, Ohsaka, STOC 2024].